Global marketing management - Kotabe, Masaaki; Helsen, Kristiaan (New York : John Wiley and Sons, 2001)
This book is about: Globalization; Global marketing environment; Development of competitive marketing strategy; Global marketing strategy development; ...
Keywords: Business; Management; Enterprises; Export marketing; Export marketing -- Management; International business enterprises -- Management